TOURISM AREA LIFE CYCLE (TALC) UNTUK PEMBANGUNAN LINGKUNGAN BERKELANJUTAN DI KAWASAN EKOWISATA GANCIK HILL TOP, BOYOLALI, JAWA TENGAH - Chandra Puspita Sari; Fuad Muhammad; Hadiyanto _ (PROSIDING SNAST, 2018)
Tourism development must be based on sustainability criteria, which means that it must be ecologically sustainable in the long term, and economically feasible, and ethically and socially equitable for local communities. The development of a tourist object cannot be separated from the examination of physical and psychological factors that affect the life cycle of an area which ultimately leads to decline. The development of the tourism world encourages further research in each tourist destination because each region has different characteristics, so dynamism of a tourism area management is possible. A tourist area will experience a cycle (TALC) that is divided into seven stages along with the characteristics at each stage. Methodology was carried out by observing and interviewing about the development of tourist destinations and analyzing the number of tourist visits in a few months so that one cycle was obtained. This theory is used in Gancik Hill Top tourist attractions in order to find out the existence of the attraction of the region. This theory is also applied to see the characteristics of existing infrastructure in the region. Since it opened in 2015, an increase in the number of tourist visits is increasingly visible. Data from March - June 2018 visits saw a 56% increase in tourist visits for tourist destinations, and 37% for climbers. In addition, there is an increase in outside investor capital, growth of tourism organizations, more adequate facilities, providers of foreign tourism services and artificial tourist attractions as well as more physically opening tourist destinations.